Towards coopetition in sport. Challenges for the market of high competition - Stosik, Aneta; Leśniewska, Aleksandra (Quality in Sport, 2016)
One of the most important aspects of leading service organizations is searching for advantages and creative solutions. Organizations look for new qualitative assets, create new values for their clients and create processes on the basis of their key competences. That kind of approach enable to improve organizational effectiveness and economic efficiency but more important to gain competitive advantages. Sport and recreational services develops extremely dynamically. Changes of lifestyle and social norms impose on clients non-standard actions and looking for individualized services. Personal training became a response for specific client’s needs. Personal trainers help not only to shape bodies and build fitness for clients, but also provide professional and individualized services by their competency complementarity. To achieve this personal trainers need to look for support and cooperation with other specialists and trainers in the whole customer service process. Building competitive advantages by cooperation with competitors cause a situation where personal trainers have to cooperate and compete with them at the same time - this phenomenon is called co-opetition and becomes more often a standard in recreational services.